Tracking Economic Activity in Response to the COVID-19 Crisis Using Nighttime Lights : The Case of Morocco - Roberts, Mark (World Bank, Washington, DC, 2021)
Over the past decade, nighttime lights have become a widely used proxy for measuring economic activity. This paper examines the potential for high frequency nighttime lights data to provide “near real-time” tracking of the economic impacts of the COVID-19 crisis in Morocco. At the national level, there exists a strong correlation between quarterly movements in Morocco’s overall nighttime light intensity and movements in its real GDP. This finding supports the use of lights data to track the economic impacts of the COVID-19 crisis at higher temporal frequencies and at the subnational level, for which GDP data are unavailable. Consistent with large economic impacts of the crisis, Morocco experienced a large drop in the overall intensity of its lights in March 2020, from which it has subsequently struggled to recover, following the country’s first COVID-19 case and the introduction of strict lockdown measures. At the subnational level, while all regions shared in March’s national decline in nighttime light intensity, Rabat – Salé – Kénitra, Tanger – Tetouan – Al Hoceima, and Fès – Meknès suffered much larger declines than others. Since then, the relative effects of the COVID-19 shock across regions have largely persisted. Overall, the results suggest that, at least for Morocco, changes in nighttime lights can help to detect the timing of changes in the direction of real GDP, but caution is needed in using lights data to derive precise quantitative estimates of changes in real GDP.